2011
DOI: 10.1292/jvms.10-0247
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S3 Immunoreactivity in the Young, Adult and Aged Gerbil Hippocampus

Abstract: ABSTRACT. Ribosomal protein S3 (rpS3) is well known to participate in DNA repair mechanisms. In the present study, we compared rpS3 immunoreactivity and its protein levels in the hippocampus among young, adult and aged gerbils. In the postnatal month (PM) 3 group as the young, rpS3 immunoreaction was observed in pyramidal and non-pyramidal cells of the hippocampus proper and in granule and polymorphic cells of the dentate gyrus. In the PM 12 group as adult and 24 group as the aged, rpS immunoreactivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…It was reported that rpS3-immunoreactive neurons were well observed in the hippocampus, especially, in the pyramidal cells of the CA1-3 regions and in the granule cells of the dentate gyrus (Hwang et al 2008;Lee et al 2011). Our present study showed that rpS3 immunoreactivity in pyramidal and granule cells began to decrease from 6 h after LPS treatment and hardly detected from 1 day after LPS treatment.…”
Section: Discussionsupporting
confidence: 60%
“…It was reported that rpS3-immunoreactive neurons were well observed in the hippocampus, especially, in the pyramidal cells of the CA1-3 regions and in the granule cells of the dentate gyrus (Hwang et al 2008;Lee et al 2011). Our present study showed that rpS3 immunoreactivity in pyramidal and granule cells began to decrease from 6 h after LPS treatment and hardly detected from 1 day after LPS treatment.…”
Section: Discussionsupporting
confidence: 60%
“…We found in aged vs. young mice that a large number of cytoplasmic ribosomes-related proteins were decreased in the hippocampus but not significantly altered in the cerebral cortex. In addition, it is well known that translation of ribosomal protein L4 (RPL4) is necessary for rapid axonal regeneration [61] and ribosomal protein S3 (RPS3) is involved in DNA repair mechanisms [62]. In sum, the overall decrease of ribosomal proteins may be closely related to the physiology of brain aging.…”
Section: Cytoplasmic Ribosomesmentioning
confidence: 99%
“…The fibrinogen A (FGA), along with SERPINA1 and platelet basic protein (PPBP), has a role in hemostasis ( Rau et al, 2008 ; Smyth et al, 2009 ; Sørensen et al, 2011 ) preventing blood loss. The FAU, or 40S ribosomal protein S30, has a role in DNA repair and function (DNA damage), which seemed to lower in AD brain ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%